Cáncer de colon hereditario - Blanco, Ignacio; Cabrera, Esther; Llort, Gemma (Psicooncología, 2005)
Colorrectal cancer (CCR) is one of the most common cancers worldwide. In developed countries, it is the second most common cancer both in men and women, after breast and lung cancer, respectively. When both sexes are considered jointly, it occupies the first place in incidence and represents the second cause of death by cancer.In the last years we have attended a very significant advance in the knowledge of the mechanisms that participate in the development and progression of CCR. These advances include the identification of novel cancer genes that have provided fundamental insights into the mechanism of carcinogenesis that will ultimate translate into cancer prevention and treatment. In particular, the demonstration of the premalignant potential of the colorectal adenoma and the identification of the genes responsible for the hereditary forms of CCR have given foot to diverse preventive strategies that can significantly contribute to diminish the incidence and the morbi-mortality of CCR